2021
DOI: 10.3389/fgene.2021.666648
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up in Patients With Non-invasive Prenatal Screening Failures: A Reflection on the Choice of Further Prenatal Diagnosis

Abstract: BackgroundOur aim was to provide a theoretical basis for clinicians to conduct genetic counseling and choose further prenatal diagnosis methods for pregnant women who failed non-invasive prenatal screening (NIPS).MethodsA retrospective analysis was performed on pregnant women who had failed NIPS tests.ResultsAmong the 123,291 samples, 394 pregnant women did not obtain valid results due to test failures. A total of 378 pregnant women were available for follow-up, while 16 patients were lost to follow-up. Of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Next, 20 µl of cfDNA libraries was constructed by end filling and adapter ligation, and qPCR analysis was performed to verify whether the concentration and quality of cfDNA libraries were satisfactory. The cfDNA libraries were subjected to massive parallel sequencing using the NextSeq CN500 high-throughput sequencing kit (Illumina) on a NextSeq CN500 platform (Illumina), generating approximately 5 million raw data with 36-bp reads ( Liu et al, 2021 ).…”
Section: Maternal Serum Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, 20 µl of cfDNA libraries was constructed by end filling and adapter ligation, and qPCR analysis was performed to verify whether the concentration and quality of cfDNA libraries were satisfactory. The cfDNA libraries were subjected to massive parallel sequencing using the NextSeq CN500 high-throughput sequencing kit (Illumina) on a NextSeq CN500 platform (Illumina), generating approximately 5 million raw data with 36-bp reads ( Liu et al, 2021 ).…”
Section: Maternal Serum Screeningmentioning
confidence: 99%
“…Sequencing reads were uniquely mapped to the hg19 human reference genome. The Z -score values of the 24 chromosomes were further calculated using normalized chromosome representation and GC correction ( Liu et al, 2021 ). The fetal autosomal trisomy status was determined based on Z -scores (normal range, −3 < Z < 3).…”
Section: Maternal Serum Screeningmentioning
confidence: 99%
“…Our analysis revealed that the fetal fraction decreases with an increase in BMI, which was in line with previous results ( 10 ). In addition, our previous study analyzed test failure cases of NIPS, and the primary reason (79.44%) for test failure in 394/123,291 cases was fetal fraction <4%, other reasons included sequencing failure and DNA concentration higher than the quality control standard ( 12 ). The gestational age of the low fetal fraction group was 17.40 ± 2.27 weeks and the BMI was 25.66 ± 3.67 kg/m 2 , which were significantly different from those of the sequencing failure group and the DNA concentration outside of laboratory quality control group (all P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…NIPS was performed by collecting 8–10 ml of peripheral blood from the expectant mother. Extraction of cfDNA, library construction, and massive parallel sequencing were carried out as described in a previous study ( 12 ). Fetal fraction of male and female fetuses were estimated based on the Y chromosome-based method ( 13 ) and distribution of plasma cfDNA fragment length, respectively ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…Maternal peripheral blood (10 ml) was collected in a cell-free BCT tube (Streck, Omaha, NE, United States). The procedural details of the experimental operation and analysis methods have been published previously (Liu et al, 2021). The test results for all 24 chromosomes were presented using Z-scores (normal range, −3 < Z < 3).…”
Section: Noninvasive Prenatal Screeningmentioning
confidence: 99%